Analisis Pelayanan Publik, Teknologi Informasi, Dan Kepatuhan Wajib Pajak Dalam Meningkatkan Efektivitas Penerimaan Pajak Melalui Peran Kualitas Komunikasi Pada Badan Pendapatan Daerah Kabupaten Penajam Paser Utara Provinsi Kalimantan Timur - Muryani, Sri; Hasnianty; Rukaiyah, St (Jurnal Online Manajemen ELPEI, 2024)
This aims to measure public services, information technology, and taxpayer compliance in increasing the effectiveness of tax revenue through the role of communication quality at the Regional Revenue Agency of North Penajam Paser Regency, East Kalimantan Province. This quantitative research data collection was carried out by questionnaire to 63 respondents. The results of the returned and valid questionnaires were 63 people. Data processing using descriptive statistical analysis with validity test methods, reliability tests and classical assumption tests using the SPSS program. The testing technique often used by researchers to test validity is to use path analysis. and using the questionnaire reliability test method in the study used the Cronbach's Alpha method with a correlation limit of 0.7, it is said that the item provides a sufficient level of reliability. The classic assumption test is a normality test, multicollinearity test, and heteroscedasticity test. The results of this study concluded that based on the path analysis test, the results of the direct and indirect effects of Public Services (X1), Information Technology (X2), and Taxpayer Compliance (X3) on the Effectiveness of Tax Revenue (Y) through Communication Quality (Z) showed that the direct effect was smaller than the indirect effect.